2021
DOI: 10.1002/cld.1136
|View full text |Cite
|
Sign up to set email alerts
|

CON: Liver Transplantation in the Times of COVID‐19: Patients with COVID‐19 Infection Should not Undergo Liver Transplantation

Abstract: Currently, there are insufficient data to conclude that liver transplantation (LT) is safe in patients with coronavirus disease 2019 (COVID-19) infection, because these patients may be at high risk for postoperative and COVID-19-related complications, graft loss, and death.• Transplantation despite high transmissibility places transplant health care workers at risk for contracting the virus and may place undue stress on the health care system by requiring higher utilization of hospital resources. • LT of COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Regarding the outcome of surgical procedures that were performed during the COVID-19 pandemic, published data revealed that LT patients infected with SARS-CoV-2 who underwent surgery experienced significant postoperative morbidity and mortality [ 45 ]. In a large international study of SARS-CoV-2-infected patients who underwent emergent or elective nontransplant surgeries, the 30-day mortality was found to be 21%, with nearly half of those patients developing pulmonary complications [ 46 ].…”
Section: Covid-19 and Lt Candidatesmentioning
confidence: 99%
“…Regarding the outcome of surgical procedures that were performed during the COVID-19 pandemic, published data revealed that LT patients infected with SARS-CoV-2 who underwent surgery experienced significant postoperative morbidity and mortality [ 45 ]. In a large international study of SARS-CoV-2-infected patients who underwent emergent or elective nontransplant surgeries, the 30-day mortality was found to be 21%, with nearly half of those patients developing pulmonary complications [ 46 ].…”
Section: Covid-19 and Lt Candidatesmentioning
confidence: 99%
“…Liver damage in COVID-19 may cor-relate with the overall severity of the disease and serve as a prognostic factor for the development of acute respiratory distress syndrome [2]. In addition, some studies have shown that the presence of pre-existing liver di sease in patients with COVID-19 contributes to poor clinical outcomes and should be taken seriously during treatment, particularly in liver transplant patients [3] with cirrhosis, acute liver injury [4] and COVID-19, due to an altered immune status Gastroenterologìa, ISSN 2308-2097 (print), ISSN 2518-7880 (online)…”
Section: Introductionmentioning
confidence: 99%
“…Liver transplantation (LT) is the treatment of choice for end-stage liver disease, but the continued shortage of deceased donors remains problematic. With the steady increase in LT over the last decades and the donor pool remaining largely stagnant, the shortage of organs for transplantation has become even more pressing because of the coronavirus disease 2019 (COVID-19) pandemic 1 . Living donor liver transplantation (LDLT) has been widely used worldwide and has become an effective, lifesaving alternative to deceased donor liver transplantation.…”
Section: Introductionmentioning
confidence: 99%